2023
DOI: 10.1038/s41598-023-37892-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of visceral and subcutaneous fat with bone mineral density in US adults: a cross-sectional study

Abstract: The relationship between the accumulation of fat in visceral or subcutaneous tissue and bone mineral density (BMD) remains unclear. Our primary objective in this study was to illuminate this relationship by conducting an investigation on a vast scale, encompassing a nationally representative population in the United States. A weighted multiple linear regression model was established to evaluate the relationship between visceral fat, subcutaneous fat, and BMD. Additionally, the exploration of the potential nonl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Increased fat mass up to a healthy range has traditionally been considered as ‘bone-protective’ since mechanical loading is associated with higher BMD through proliferation of osteoblasts and reduction of bone apoptosis. 54 , 55 Healthy bones respond to mechanical stress up to a reasonable limit by remodelling, and a decrease in mechanical loading through weight loss may lead to bone loss. 56 , 57 This effect may be pronounced in weight-bearing bones such as the lumbar region that was evaluated in this study and may explain our findings as the procedures that generate the most weight loss have lower BMD and Z scores.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fat mass up to a healthy range has traditionally been considered as ‘bone-protective’ since mechanical loading is associated with higher BMD through proliferation of osteoblasts and reduction of bone apoptosis. 54 , 55 Healthy bones respond to mechanical stress up to a reasonable limit by remodelling, and a decrease in mechanical loading through weight loss may lead to bone loss. 56 , 57 This effect may be pronounced in weight-bearing bones such as the lumbar region that was evaluated in this study and may explain our findings as the procedures that generate the most weight loss have lower BMD and Z scores.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ng et al [25], the relationship between visceral and subcutaneous fat depots and bone health is more complex and is specific for age, gender, menopausal status, bone compartment, and adipose depot. Lin et al [18] revealed a negative association between subcutaneous fat and lumbar spine BMD. On the other hand, a non-linear (U-shaped) relationship between visceral fat and BMD was determined.…”
Section: Interactions Between Adipose Tissue and Bone Tissuementioning
confidence: 97%
“…In general, adipose tissue is made up of adipocytes distributed in the organism, especially in the subcutaneous and visceral fat. The function of adipose tissue varies from organs as energy storage sites to endocrine organs secreting various factors that can influence different organ systems and regulate energy metabolism [3,18]. In the context of obesity and T2DM, intramuscular fat and bone marrow adipose tissue also play a significant role in skeletal homeostasis and bone fragility [4,9].…”
Section: Interactions Between Adipose Tissue and Bone Tissuementioning
confidence: 99%
“…On the other hand, increased mechanical loading resulting from elevated BMI has been linked to higher BMD and improved microstructure, thus positively impacting both cortical and trabecular bone health [244]. To reconcile conflicting results, a U-shaped correlation between visceral WAT and BMD has been proposed [245], thus further increasing the level of complexity.…”
Section: Senile Osteoporosismentioning
confidence: 99%